Pengaruh Rasio Campuran Surfaktan dan Minyak Atsiri Jahe (Zingiber Officinale Var. Amarum) terhadap Karakteristik Mikroemulsi yang Dihasilkan - Dwipayana, I Made; Suhendra, Lutfi; Triani, I Gusti Ayu Lani (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 1 (2022): Maret, 2022)
This study aims to determine the effect of the mixture ratio of surfactant and ginger essential oil on the characteristics of the resulting microemulsion and determine the best ratio of surfactant and ginger essential oil mixture to obtain the best microemulsion characteristics. This experiment used a simple randomized block design (RAK) with a mixture ratio of surfactant and ginger essential oil: 100:0; 98:2; 96:4; 94:6; 92:8; 90:10; 88:12; 86:14; 84:16; 82:18. Data were analyzed using analysis of variance and continued with the BNJ test. The best treatment was the highest ratio of ginger essential oil which still formed microemulsion. The microemulsion with the best ratio was tested for stability against pH and dilution during 8 weeks of storage with observations every 2 weeks. Data were analyzed using linear regression to determine the stability of ginger essential oil microemulsion. The results showed that the ratio of the mixture of surfactants and ginger essential oil had an effect on the characteristics of the resulting microemulsion. The ratio of surfactant and ginger essential oil 96:4 is the best treatment for making ginger essential oil microemulsion with the characteristics of having a transparent microemulsion appearance, turbidity index values before and after centrifugation of 0.225±0.011% and 0.294±0.008% and having a particle size of 12, 5±5.0 nm, the largest droplet size was 11 nm, and was stable for 8 weeks of storage. Keywords: microemulsion, surfactant, ratio, Zingiber Officinale var. Amarum